2015
DOI: 10.2141/jpsa.0130211
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Prebiotics, Probiotics, and Synbiotics on Laying Hens and Broilers Challenged with Salmonella Enteritidis

Abstract: This study aimed to evaluate the efficacy of dietary prebiotic, probiotic, and synbiotic products for controlling infection in laying hens and broiler chickens challenged with Salmonella enterica serovar Enteritidis (SE). These products could replace the use of antibiotics, which would avoid the problem of hastening antimicrobial resistance for both types of birds. Salmonella-free 1-day-old (1-d-old) layers chicks and broilers chicks were inoculated with SE resistant to nalidixic acid and spectinomycin (SE Nal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
(21 reference statements)
0
22
0
1
Order By: Relevance
“…who reported that dietary 2 g kg –1 synbiotics, irrespective of resources, did not alter fecal E. coli counts in piglets. Similarly, Sayuri Murate et al . have also shown that the supplementation of 1.0 g kg –1 synbiotic did not affect the viable number of Salmonella enteritidis in the cecal content of broilers challenged with S. enteritidis .…”
Section: Discussionmentioning
confidence: 81%
“…who reported that dietary 2 g kg –1 synbiotics, irrespective of resources, did not alter fecal E. coli counts in piglets. Similarly, Sayuri Murate et al . have also shown that the supplementation of 1.0 g kg –1 synbiotic did not affect the viable number of Salmonella enteritidis in the cecal content of broilers challenged with S. enteritidis .…”
Section: Discussionmentioning
confidence: 81%
“…Historically, probiotic utilization in the poultry industry has been viewed as an alternative to antibiotics that promoted a “healthy” intestinal microbiota ( Mátéová et al., 2008 ; Katoch et al., 2013 ; Vandana et al., 2013 ), improved growth rates, limited animal diseases ( Gorbach, 2000 ; Nava et al., 2005 ; Ghareeb et al., 2008 ; Callaway et al., 2012 ), and inhibited foodborne pathogen growth ( Patterson and Burkholder, 2003 ; Lutful Kabir, 2009 ; Murate et al., 2015 ; Olnood et al., 2015 ; Penha Filho et al., 2015 ; Upadhaya et al., 2016 ). There are currently a vast number of probiotic products in the marketplace being promoted to improve poultry production efficiency, health, and safety.…”
Section: Probiotics – General Concepts and Definitionsmentioning
confidence: 99%
“…Although the exact physiological mechanisms of feed additives are unclear, the health effects are focused on the gut ( Dibner and Richards, 2005 ; Krysiak et al, 2021 ). Probiotics are valuable gut microbe species that can colonize the gut, and prebiotics is indigestible oligosaccharides that can be utilized by the useful gut microbes ( Wenk, 2000 ; Kulshreshtha et al, 2014 ; Murate et al, 2015 ). Endogenous enzymes such as carbohydrases and proteases are used to increase the digestibility of feed in the gut ( Wenk, 2000 ; Sharma et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%